2008
DOI: 10.2174/157489008786263989
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Sirt1 and Sirt1 Modulators in Cardiovascular and Metabolic Diseases

Abstract: Sirt1 (member of the sirtuin family) is a nicotinamide adenosine dinucleotide (NAD)-dependent deacetylase that removes acetyl groups from various proteins. A wide variety of proteins are Sirt1 substrates; the list includes many transcription factors and cofactors. Deacetylation of these factors may lead to activation or inactivation of the factor, thus impacting downstream gene expression. In addition to direct deacetylation, Sirt1 can modulate protein activity by other mechanisms. Although initial research fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 0 publications
0
89
0
Order By: Relevance
“…The inducible Sirt1 Ϫ/Ϫ mice used in our studies may mimic some of the responses to PM 2.5 exposure in aging. [21][22][23][24][25][26] Our study suggests that decreased Sirt1 expression in the elderly could be a potential risk factor for PM-induced coagulation and inflammation.…”
Section: Sirt1 Controls Lung Inflammation and Coagulation 2427mentioning
confidence: 68%
See 2 more Smart Citations
“…The inducible Sirt1 Ϫ/Ϫ mice used in our studies may mimic some of the responses to PM 2.5 exposure in aging. [21][22][23][24][25][26] Our study suggests that decreased Sirt1 expression in the elderly could be a potential risk factor for PM-induced coagulation and inflammation.…”
Section: Sirt1 Controls Lung Inflammation and Coagulation 2427mentioning
confidence: 68%
“…[21][22][23][24][25][26] NF-B, a transcription factor that regulates inflammatory responses, is an endogenous substrate for Sirt1. [27][28][29][30] It has been reported that Sirt1 deacetylates NF-B, thereby inhibiting its activity in several in vitro and in vivo systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies point to Sirt1 as a chief regulator of NO synthesis in endothelium (Milne et al 2007;Pillarisetti 2008;Potente et al 2007) employing an Akt-mediated pathway of eNOS phosphorylation (Lovren et al 2009) or promoting eNOS catalytic activity through deacetylation of lysines 496 and 506 (Mattagajasingh et al 2007). As NO itself appears to reciprocally activate Sirt1 expression and activity (Ota et al 2007), then Sirt1-eNOS axis emerges as a decisive regulatory mechanism in CC endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…During chronic pressure overload such as in chronic hypertension, PGC1α gene controls fatty acid oxidation and Tfam gene increases number of mitochondria are downregulated which is consistant with the fact that mitochondrial respiratory function is reduced during end-stage heart failure [32].…”
Section: Discussionmentioning
confidence: 99%